DESIGN AND EVALUATION OF A CONSTRUCT 3-BASED EDUCATIONAL GAME TO PROMOTE LEARNING ON SDG 7: AFFORDABLE AND CLEAN ENERGY - Julietta Tsuraya Puspa Rannie; Erna Suhartini; Mustamiroh Mustamiroh; Muhlis Muhlis (Lembaga Penelitian Mahasiswa Penalaran UNM, 2025)
This research develops a Construct 3-based educational game integrated with Sustainable Development Goal 7 (Affordable and Clean Energy) for fourth-grade elementary students, with a focus on energy materials. Employing Research and Development methodology with the ADDIE model, the study involved 27 students and one teacher at SDN 007 Samarinda Ilir. The research instruments consisted of interview sheets, needs questionnaires, expert validation forms, and user response questionnaires. Expert validation yielded 92% feasibility ratings from media specialists and 89.3% from material experts, both of which were rated as